2017
DOI: 10.1002/anie.201611536
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Friedel–Crafts C−H Borylation of Electron‐Rich Arenes: Dramatic Rate Acceleration by Added Alkenes

Abstract: In the electrophilic C-H borylation of electron-rich aromatic compounds with catecholborane, the catalytic generation of the boron electrophile is initiated by heterolysis of the B-H bond by various Lewis and Brønsted acids, with a boronium ion formed exclusively. After ligand dissociation, the corresponding borenium ion undergoes regioselective electrophilic aromatic substitution on aniline derivatives as well as nitrogen-containing heterocycles. The catalysis is optimized using B(C F ) as the initiator and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 69 publications
2
74
1
1
Order By: Relevance
“…The examples shown were used in recent studies by the groups of Ingleson, Fontaine and Repo et al., respectively. We have now found that borylation of arenes and heteroarenes with replacement of a C−H bond by the respective C−Bcat (or in a few cases C−Bpin) functionalities can very efficiently be carried out under mild conditions using some specific geminal bis‐borane catalysts featuring strongly electrophilic BC 6 F 5 moieties . First representative examples of such metal‐free catalytic heteroarene borylation reactions will be described in this account.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The examples shown were used in recent studies by the groups of Ingleson, Fontaine and Repo et al., respectively. We have now found that borylation of arenes and heteroarenes with replacement of a C−H bond by the respective C−Bcat (or in a few cases C−Bpin) functionalities can very efficiently be carried out under mild conditions using some specific geminal bis‐borane catalysts featuring strongly electrophilic BC 6 F 5 moieties . First representative examples of such metal‐free catalytic heteroarene borylation reactions will be described in this account.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the HBcat p ‐borylation of the derivatives 10 b , c catalyzed by 4 gave the products 12 b (78 %) and 12 c (88 %), respectively (see the Supporting Information for their characterization). On the basis of the respective literature precedence, we assume a pathway that involves formation of reactive borenium‐type intermediates by means of hydride transfer to the chelate bis‐borane catalysts. We carried out a similar experiment as described by Oestreich et al.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, the eliminated proton from the enol form can activate the keto form of 1 a by generating a Lewis acid ( + NH 2 (Me) 2 ). Here, the proton-shuttling [28] action of dimethylamine facilitats the formation of the persistent ketyl radical A and transient a-carbonyl radical B by fac-Ir(ppy) 3 under visiblelight irradiation. As a result, the transient a-carbonyl radical B could be selectively intercepted by alkynes to synthesize 1naphthols 8-1 and the persistent ketyl radical A dimerizes to pinacols 9 a + 9 a'.…”
Section: Photoredox Catalysis Of Aromatic B-ketoesters For In Situ Prmentioning
confidence: 98%
“…In a few cases, Friedel-Crafts-type catalysis could be observed for the TM-free catalytic borylation of arenes, in mechanisms that bear little similarity to TM chemistry. 152,154,158,[161][162][163] Similar reactions are typically metal catalyzed, 164,165 often by precious metals such as iridium or palladium, which act in tandem with an internal base.…”
Section: Arene C-h Activationmentioning
confidence: 99%